T&V Has a High Payoff - World Bank (Washington, DC, 2012)
T&V has a high payoff. A new approach to petroleum exploration. More books for schools, by A. Buchan, C. Denning, T. Read, D. Lacase, and S. Diop. Better transport, by Phillip Moeller and S. Carapetis et al. A new deal for mining. Public examinations: problem or solution, by Kelleghan and Greaney. Nexus update. A comprehensive approach to land management, by Walter J. Lusigi and Bengt A. Nekby. Agriculture research to be revitalized.